Epidemiological and economic aspects of diabetes in the Campania Region, Italy - Cammarota, Simona; Morsanutto, Andrea; Menditto, Enrica; Citarella, Anna; de Portu, Simona (Farmeconomia. Health economics and therapeutic pathways, 2008)
Aim: to assess the economic and epidemiologic impact of diabetes in Campania, a region of approximately 5.7 million inhabitants in the south of Italy. Method: we collected, from an electronic database, all prescriptions for antidiabetic drugs reimbursed in the first half year of 2005 in 8 local health authorities (60% of the overall population) of Campania. The diabetic cohort was defined as the population of subjects receiving at least 2 prescriptions of an antidiabetic agent in 6-month, classified according to their therapeutic role using Anatomic Therapeutic Chemical (ATC) classification. Characterization is given of the patients and their antidiabetic medication. Subsequently, the prescription of concomitant treatment, in comparison with a control group, is presented. Drugs cost and drugs consumption were quantified using NHS prospective (expressed in Euro 2005) and Defined Daily Dose system (DDD) respectively. Results: the diabetic cohort included 183,614 subjects (5.3% of the observed population), mean age was 65.0 years and female represented 54.8% of the sample. Total cost for diabetic patients represents 16.8% of the total drug expenditure. The average drug/cost/patient was € 355.7; only 19.0% was spent for antidiabetic drugs. The reported use of medication was higher for subjects with diabetes compared with the control population regarding overall use (2,363.5 versus 1259.8 DDD/1,000 inhabitants/die), the use of cardiovascular drugs (1,499.3 versus 663.5 DDD/1,000 inhabitants/day), use of haematologic drugs (277.1 versus 120.3 DDD/1,000 inhabitants/day), and use of ophthalmological drugs (48.3 versus 21.0 DDD/1,000 inhabitants/day). Discussion: chronic-degenerative pathologies, such as diabetes, implies a relevant social and economic impact. Expenses that are associated to the treatment and the prevention of complications, in particular cardiovascular problems, are registered among the main items listed in the healthcare budget.